Agent-based simulation with awareness levels of the emergency evacuation of educational facilities - Sharbini, Hamizan; Chan, Chiu Po; Mat, Abdul Rahman; Borhan, Noor Hazlini; Talib, Mohamad Shukor; Mustaffa, Noorfa Haszlinna (Edelweiss Applied Science and Technology, 2025)
In this study, we explore the impact of awareness levels on emergency evacuation efficiency in educational settings, specifically classrooms, by modeling crowd behavior using agent-based simulation. An agent-based simulation was developed using NetLogo to model autonomous agents navigating an evacuation scenario with and without awareness levels. The environment included classroom layouts with obstacles and single exit points. Simulation data were analyzed statistically using SPSS, including ANOVA and PostHoc testing, to evaluate differences in evacuation performance. The results indicate that awareness levels lead to consistently lower evacuation times across varying crowd sizes (10 to 50 agents). With awareness, the average evacuation time remained nearly constant, whereas without awareness it increased notably with crowd size. Statistical tests confirmed a significant difference (p = 0.031) between the two conditions. While the absolute reduction in evacuation time is modest, awareness helps maintain evacuation efficiency as crowd size increases, highlighting its stabilizing effect. Integrating awareness into evacuation models offers valuable insights for enhancing emergency preparedness in schools. The simulation tool can support planning, training, and the design of spatial layouts to improve safety outcomes during emergencies.